Quantitative and qualitative comparison of a new prosthetic suspension system with two existing suspension systems for lower limb amputees - Eshraghi, A.; Abu Osman, Noor Azuan; Karimi, M.T.; Gholizadeh, H.; Ali, S.; Wan Abas, Wan Abu Bakar (Lippincott, Williams & Wilkins, 2012)
OBJECTIVE: The objectives of this study were to compare the effects of a newly designed magnetic suspension system with that of two existing suspension methods on pistoning inside the prosthetic socket and to compare satisfaction and perceived problems among transtibial amputees. DESIGN: In this prospective study, three lower limb prostheses with three different suspension systems were fabricated for ten transtibial amputees. The participants used each of the three prostheses for 1 mo in random order. Pistoning inside the prosthetic socket was measured by motion analysis system. The Prosthesis Evaluation Questionnaire was used to evaluate satisfaction and perceived problems with each suspension system. RESULTS: The lowest pistoning motion was found with the suction system compared with the other two suspension systems (P < 0.05). The new suspension system showed peak pistoning values similar to that of the pin lock system (P = 0.086). The results of the questionnaire survey revealed significantly higher satisfaction rates with the new system than with the other two systems in donning and doffing, walking, uneven walking, stair negotiation, and overall satisfaction (P < 0.05). CONCLUSIONS: The new suspension system has the potential to be used as an alternative to the available suspension systems. The pistoning motion was comparable to that of the other two systems. The new system showed compatible prosthetic suspension with the other two systems (suction and pin lock). The satisfaction with donning and doffing was high with the magnetic system. Moreover, the subjects reported fewer problems with the new system.